Pengaruh Konvergensi IFRS, Etnisitas dan Subsidiaries terhadap Audit Fees - Lodovicus Lasdi; Helen Sylviana; Teodora Winda Mulia (LPPM UBP, 2024)
Companies are required to prepare financial reports as a form of transparency and accountability in the financial sector. In addition, financial reports are also used by stakeholders and other stakeholders to make decisions. To ensure that the report is reasonable and reliable, the financial statements must be audited by an independent auditor. The objective of the financial report audit is to ensure the reliability of the financial statements prepared by management. Auditors must be competent in understanding the client's business, determining the amount of business risk, and the complexity of the business, which will impact on the amount of fees or audit fees. Currently, the amount of audit fees is still an interesting thing to study. Audit fees are fees charged by the auditor in the audit process to the company being audited. There are several factors that influence the determination of audit fees, namely convergence of International Financial Reporting Standards (IFRS), company size, ethnicity, subsidiaries, business complexity and audit committee.